A multifunctional ultra-thin acoustic membrane with self-healing properties for adaptive low-frequency noise control - Marco Boccaccio; Konstantinos Myronidis; Michael Thielke; Michele Meo; Fulvio Pinto (Scientific Reports, 2022)
Abstract This paper proposes a novel multifunctional ultra-thin membrane based on a Polyborosiloxane-based gel with stimuli-responsive sound absorption and sound transmission loss (STL) and characterised by excellent self-healing properties. This adaptive behaviour is the result of a dynamically activated phase transition in the membrane’s polymeric network which is given by the interaction with the travelling sound pressure wave. The presence and the extent of such phase transition in the material was investigated via oscillatory rheological measurements showing the possibility to control the dynamic response by modifying the Boron content within the polymer. Acoustic analyses conducted at different stimuli responses showed high and dynamic absorption (95%) at the absorption coefficient peaks and an adaptive shift to lower frequencies while sound amplitudes were increased. An average STL up to 27 dB in the frequency range between 500 to 1000 Hz was observed and an increased STL above 2 dB was measured as the excitation amplitude was increased. Results demonstrated that the new membrane can be used to develop deep subwavelength absorbers with unique properties (1/54 wavelength in absorption and 1/618 in STL) able to tune their performance in response to an external stimulus while autonomously regaining their properties in case of damage thanks to their self-healing ability.